Single-processor scheduling problems with both learning and aging effects - Rudek, Radosław (Jednoprocesowe problemy harmonogramowania z efektem uczenia i zużycia, 2011)
In this paper, we analyse single processor scheduling problems with both learning and aging effects to minimize the following criteria: the maximum completion time with release dates, the maximum lateness and the number of late jobs. The learning effect can be understood as a process of an acquiring experience that leads to increasing efficiency of a processor, which results in decreasing processing times of jobs. The opposite phenomenon called the aging effect decreases the efficiency of a processor. The measurable result of this effect is that the time required to process a single item decreases as more units are processed. We prove properties of the investigated problems and on their basis we provide optimal polynomial-time algorithms for some cases
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 206, s. 173-182
Keywords: scheduling; learning effect; aging effect; polynomiail-time algorthitm; harmonogramowanie; efekt uczenia; efekt starzenia; wielomianowe optymalne algorytmy